The creation of fiscal space for the property tax: the case of Central and Eastern Europe - J. McCluskey, William; Plimmer, Frances (International Journal of Strategic Property Management, 2011)
The case for the property tax as a significant revenue generator has been well made by many eminent scholars in public finance. It nonetheless continues to remain a tax that is under-utilised in many transition countries. The purpose of this paper is to investigate whether there is the fiscal space to develop the property tax within the eight CEE1 countries that joined the EU in May 2004. Currently, property tax revenues within the selected countries represent approximately 0.5% of GDP, whilst the average for the OECD is just over 1%. This difference in relative importance would appear to suggest that, whilst there is potential for the property tax to create greater revenues, there are structural problems that are preventing this. The paper highlights a number of these problems and suggests mechanisms to address them. It is argued that properly designed, the property tax could crowd out many of the ‘nuisance’ taxes and fees that already exist within local government.First Publish Online: 4 Jul 2011